2018
DOI: 10.3390/su10103579
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of the Visual Comfort Performance between a PCM Glazing and a Conventional Selective Double Glazed Unit

Abstract: The performance of a Double Glazing Unit (DGU) with a Phase Change Material (PCM) layer embedded in the cavity was analyzed in terms of the visual comfort perceived by the occupants. The analysis was carried out through a set of simulations, performed by the Radiance engine managed through Honeybee. As an input for the simulations, the visible transmittance Tv of PCM in solid (diffusing) state was used, based on previous laboratory measurements. The simulations were run for several specific times of the year: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
4
0
1
Order By: Relevance
“…As shown in Figures 14-19, the variation of the illuminance of each material over time is distributed over time and appears in a "W" shape, assuming that cloud interference is excluded [19][20][21][22]. The illumination intensity of each dot zone of each material will reach a small peak at 12:30 because the solar altitude angle is the highest and the light intensity is strongest at noon, and the illumination of each dot zone at 11:30 and 13:30 is lower than the value of 12:30.…”
Section: Data Processing and Analysismentioning
confidence: 99%
“…As shown in Figures 14-19, the variation of the illuminance of each material over time is distributed over time and appears in a "W" shape, assuming that cloud interference is excluded [19][20][21][22]. The illumination intensity of each dot zone of each material will reach a small peak at 12:30 because the solar altitude angle is the highest and the light intensity is strongest at noon, and the illumination of each dot zone at 11:30 and 13:30 is lower than the value of 12:30.…”
Section: Data Processing and Analysismentioning
confidence: 99%
“…Alguns autores apresentaram aplicações vantajosas para essa característica, como a utilização do sistema como proteção solar (GOIA; PERINO; SERRA, 2014). Porém, mesmo a utilização apenas de iluminação difusa deve ser avaliada, já que pode acarretar desconforto luminoso interno e ofuscamento (GIOVANNINI et al, 2018).…”
Section: Fechamentos Translúcidosunclassified
“…The energy performance of PCMs was investigated for a standard window component [10], as well as for unusual applications such as thermotropic glazing [14] or double skin facades [15]. Moreover, some authors showed a beneficial effect on daylight provision [2] and visual comfort [16]. In some cases, the PCM glazing can be treated as an alternative to dynamic shading systems like exterior perforated louvers [17] or other types of blinds [18].…”
Section: Introductionmentioning
confidence: 99%